Fluorescence polarization assay for diagnosis of human brucellosis - Lucero, Nidia E. (2003)
Fluorescence polarization immunoassay (FPA) uses molecular rotational properties to measure antibody binding toantigendirectly. Thepotential useof thismethodwas assessed incomparison to a competitive enzyme immunoassay (CELISA) and conventional serological tests for the diagnosis of brucellosis on a total of 587 human sera. Based on 340 sera from asymptomatic blood donors with no evidence of brucellosis, the specificity of the FPAwas97·9% using a cut-off value of 72mP. Sera fromBrucella-infected patients (11Brucellamelitensis,32Brucella abortus,32Brucella suis and oneBrucellasp.) yielded a sensitivity estimate of 96·1%. In tests on 84 sera from suspected brucellosis patients, the FPA detected 80 cases. Of 87 sera from patients with probable infection, 15 were detected by both CELISA and FPA, three by CELISA only and four by FPA only. The discrepancies inbothgroups involvedserawith low, declining titres. TheFPAuses a sampleof 40 l serum, takesabout 5 min tocompleteandhasbeendemonstrated tobeaccurate for thedetectionof antibodies toB. abortus, B. melitensisandB. suisand for identifying patients suffering relapses. Because of the ease of the procedure, it could be readily adopted for use in clinical laboratories and blood banks.